2006
DOI: 10.1016/j.neuron.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Environment Matters: Synaptic Properties of Neurons Born in the Epileptic Adult Brain Develop to Reduce Excitability

Abstract: Neural progenitors in the adult dentate gyrus continuously produce new functional granule cells. Here we used whole-cell patch-clamp recordings to explore whether a pathological environment influences synaptic properties of new granule cells labeled with a GFP-retroviral vector. Rats were exposed to a physiological stimulus, i.e., running, or a brain insult, i.e., status epilepticus, which gave rise to neuronal death, inflammation, and chronic seizures. Granule cells formed after these stimuli exhibited simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
202
6
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(231 citation statements)
references
References 70 publications
19
202
6
4
Order By: Relevance
“…However, in contrast with WT animals, the dramatic increase of proliferation we observed in Cdk6 À/À mice following KA administration did not lead to a proportional increase of newborn neuron production. These findings suggest that a pharmacological inhibition of Cdk6 may be effective in preventing the production of ectopic granule cell neurons, a putative cause of temporal lobe epilepsy in humans [55,56]. More generally, our results underline the need to decipher the distinct molecular mechanisms controlling G 1 in the different proliferating populations of the adult brain in normal or pathological conditions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, in contrast with WT animals, the dramatic increase of proliferation we observed in Cdk6 À/À mice following KA administration did not lead to a proportional increase of newborn neuron production. These findings suggest that a pharmacological inhibition of Cdk6 may be effective in preventing the production of ectopic granule cell neurons, a putative cause of temporal lobe epilepsy in humans [55,56]. More generally, our results underline the need to decipher the distinct molecular mechanisms controlling G 1 in the different proliferating populations of the adult brain in normal or pathological conditions.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to transiently enhancing cell proliferation, seizures have been shown to increase the production of newborn neurons [51]. Importantly, these newborn neurons exhibit dramatic changes of neuronal polarity and migration, and integrate aberrantly into the pre-existing neuronal network [52][53][54], leading to longterm structural changes in the hippocampal circuitry that might contribute to chronic epilepsy [55,56]. To evaluate the consequences of Cdk6 deficiency on seizure-induced neurogenesis, we injected WT and Cdk6 À/À animals with BrdU 72 hours following seizure induction and sacrificed the animals 4 weeks later to quantify the number of BrdU þ surviving cells.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 99%
“…The reported physiological and functional ramifications of SE-induced SGZ cell proliferation are quite varied. Recently, Jakubs et al (2006) reported that under epileptic conditions, newborn granule cells have reduced excitatory input and increased inhibitory input. Thus, these neurons could have beneficial effects by increasing the threshold for seizure propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings were made in hippocampal slices cultured for 3 weeks (30). Intrinsic membrane properties of whole-cell recorded neurons, as well as rheobase and action potential accommodation at strong depolarizations, were determined as previously (ref.…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsic membrane properties of whole-cell recorded neurons, as well as rheobase and action potential accommodation at strong depolarizations, were determined as previously (ref. 30; SI Methods). Rebound action potentials after light illumination (rebound) were compared with rebound action potentials induced by current injections (SI Methods).…”
Section: Methodsmentioning
confidence: 99%